2009
DOI: 10.4085/1062-6050-44.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Explosive Strength Imbalances in Professional Basketball Players

Abstract: The relative isokinetic and functional performances of professional basketball players were similar to those of junior players, with no dominant-side effect. A history of knee injury in the professional athlete, however, was reflected in bilateral isokinetic and functional asymmetries and should be considered in future studies of explosive strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
125
1
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(141 citation statements)
references
References 34 publications
5
125
1
10
Order By: Relevance
“…This recommendation came from their prospective study on the effects of neuromuscular training on the incidence of knee injury in female athletes, in which they observed a reduction in knee injury for females following a specific plyometric training program. Other sports activities have been examined to investigate imbalances, for example professional and junior level basketball players were studied to determine if lower limb explosive-strength asymmetries were present compared to each other and to a control group (Schiltz et al, 2009). An isokinetic knee extensor and flexor examination was performed, as was a countermovement jump, with and without arm movement, single-leg drop jump, a 10-m sprint, and 10-second single-leg continuous jumping.…”
Section: Injury Riskmentioning
confidence: 99%
“…This recommendation came from their prospective study on the effects of neuromuscular training on the incidence of knee injury in female athletes, in which they observed a reduction in knee injury for females following a specific plyometric training program. Other sports activities have been examined to investigate imbalances, for example professional and junior level basketball players were studied to determine if lower limb explosive-strength asymmetries were present compared to each other and to a control group (Schiltz et al, 2009). An isokinetic knee extensor and flexor examination was performed, as was a countermovement jump, with and without arm movement, single-leg drop jump, a 10-m sprint, and 10-second single-leg continuous jumping.…”
Section: Injury Riskmentioning
confidence: 99%
“…In the analysis of the knee flexors, studies with futsal players (Ferreira et al, 2010) and soccer (Zakas et al, 2006;Fousekis et al, 2010;Daneshjoo et al, 2013;Silva et al, 2015) also showed lower average scores whilst other studies showed average scores higher than the athletes of this study (soccer (Da Fonseca et al, 2007), rugby (Larrat et al, 2007) and handball (González-Ravé et al, 2014). At angular speed of 240º/s, all fields of sport analyzed (soccer (Zakas, 2006), rugby (González-Ravé et al, 2014), basketball (Schiltz et al, 2009) and volleyball (Shu & Zhou, 2011)), resulted in average scores higher than in this study, for both knee extensors and flexors.…”
Section: Juliete Palandi Elizze Ziero Ducatti Michele Poletti Vinímentioning
confidence: 49%
“…Unlikely other sports such as soccer (Fousekis et al, 2010) and futsal (Ferreira et al, 2010) which have asymmetrical muscle requirements from the extensor and flexor knee muscles, the weightlifting requires bilateral symmetrical muscle functioning from these muscle groups (Preto et al, 2014;Reiser et al, 2014). In the analysis of the average PT scores of the extensor and flexor muscles at angular speed 60º/s, both limbs showed average scores higher than the average scores found in other sports such as soccer (Zakas, 2006;Fousekis et al, 2010;Eniseler et al, 2012;Daneshjoo et al, 2013), futsal (Ferreira et al, 2010), rugby (Brown et al, 2014), basketball (Schiltz et al, 2009;Carvalho et al, 2011), handball (González-Ravé et al, 2014, and volleyball (Markou & Vagenas, 2006;Shu & Zhou, 2011). However, two studies which analyzed professional soccer players showed higher average scores of flexors than the scores of the athletes of this study (Zabka et al, 2011;Daneshjoo et al, 2013).…”
Section: Juliete Palandi Elizze Ziero Ducatti Michele Poletti Vinímentioning
confidence: 85%
“…similarly, Gerodimos et al [27] demonstrated that this functional ratio increased with the growth of angular velocity. Furthermore, schiltz et al [28] revealed the results of functional H/Q at 30 deg · s -1 /240 deg · s -1 velocities to be approximately 131% (dominant limb) and approximately 126% (non-dominant limb) in professional players. Thus, the functional H/Q > 100% during fast knee extension indicated the ability of eccentrically acting hamstrings to produce a braking joint flexor moment greater than the joint extensor moment exerted by the quadriceps [14,16,21].…”
Section: Discussionmentioning
confidence: 99%